OUTCOMES OF CEMENTED BIPOLAR RADIAL HEAD ARTHROPLASTY: CASE SERIES OF 7 - Tîrnovanu Ștefan-Dragoș; Dmour Awad; Forna Norin; Puha Bogdan; Cionca Viorel-Dan; Filip Alexandru; Cozma Tudor; Popescu Dragoș-Cristian; Sîrbu Paul-Dan; Alexa Ovidiu (Romanian Journal of Oral Rehabilitation)
Aim of the study This study assesses the effectiveness of radial head prosthesis in patients with radial head fractures, examining how demographics, injury severity, and associated injuries influence recovery and functional outcomes. Material and methods A retrospective analysis was performed on patients who underwent radial head arthroplasty. This analysis delved into clinical outcomes such as range of motion, Mayo Elbow Performance score, and Quick Disabilities of the Arm, Shoulder and Hand questionnaire, as well as complications. Data on demographics, Mason classification, and associated injuries were meticulously collected and analysed to determine their impact on recovery and the effectiveness of the prosthesis. Results Radial head prosthesis generally led to improved elbow function and reduced disability, with most patients achieving excellent MEPS scores and normal range of motion. However, variability in outcomes was noted, influenced by factors such as age, severity of the initial injury, and associated injuries. Notably, while heterotopic ossifications emerged as a recurrent complication, distal radio-ulnar joint injury was identified in only one patient, suggesting its uncommon occurrence in this patient cohort. Conclusions Radial head arthroplasty significantly enhances elbow functionality in patients with severe radial head fractures, though outcomes vary based on individual factors like age and injury severity. This study’s insights into the varied implications of radial head prosthesis contribute to optimizing treatment strategies and improving patient outcomes in orthopedic practice.